A model for optimal scheduling of hydro thermal systems including pumped‐storage and wind power. Issue 12 (1st December 2013) - Helseth, Arild; Gjelsvik, Anders; Mo, Birger; Linnet, Úlfar
Abstract : This study describes a model for optimal scheduling of hydro thermal systems with multiple hydro reservoirs. Inflow to hydropower reservoirs, wind power and exogenously given prices are treated as stochastic variables. Power flow constraints are included through a linearised power flow model. A linearised representation of start‐up costs for generating units and pumps is provided. The model is well suited for medium‐ and long‐term hydro thermal generation scheduling and has the capability of capturing detailed system constraints by using a fine time resolution. The presented model is tested on a realistic representation of the Icelandic power system, considering some potential future system extensions.